2015
DOI: 10.1002/adfm.201501271
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Crystallite Orientation of Diketopyrrolopyrrole‐Based Small Molecules in Thin Films for Highly Reproducible Multilevel Memory Device: Role of Furan Substitution

Abstract: For the organic memory device with vertically arranged electrodes, controlling the film‐packing to achieve highly oriented crystallite arrangement is critical but challenging for obtaining the satisfied performance. Here, the effect of backbone planarity on the crystallite orientation is studied. Two diketopyrrolopyrrole‐based small molecules (NI2PDPP and NI2FDPP) are synthesized with increasing planarity by furan substitution for phenyl rings. Upon thin‐film analysis by atomic force microscopy, X‐ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 95 publications
2
88
0
Order By: Relevance
“…We found that bromination with liquid Br 2 was more reliable than at ypical substitution reactionw ith N-bromosuccinimide( NBS). [16] Following the completion of the bromination reactions, the intermediates could be directly used without furtherp urification. These compounds were characterizedb yN MR spectroscopy.I fa ppended with long side chains, all three final products were soluble in commono rganic solvents, such as CHCl 3 ,t oluene, and orthodichlorobenzene.…”
Section: Resultsmentioning
confidence: 99%
“…We found that bromination with liquid Br 2 was more reliable than at ypical substitution reactionw ith N-bromosuccinimide( NBS). [16] Following the completion of the bromination reactions, the intermediates could be directly used without furtherp urification. These compounds were characterizedb yN MR spectroscopy.I fa ppended with long side chains, all three final products were soluble in commono rganic solvents, such as CHCl 3 ,t oluene, and orthodichlorobenzene.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important ingredients is the data storage component. Therefore, tremendous efforts focus on the investigation of new flexible memories which own nonvolatile capability, high‐density storage, fast switching, and reliable endurance property …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Amongt he variety of organic materials used, small molecules show the meritso fw ell-definedm olecular structures, reproducible preparation,f acile purification, and easy functionalization. [12][13][14][15][16][17] Several kinds of molecular dyes have been reported for applications in electronic memory. [12][13][14][15][16][17] Several kinds of molecular dyes have been reported for applications in electronic memory.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Moreover, organic molecules were the most promising in devicem iniaturization and three-dimensional architecture. [12][13][14][15][16][17] Several kinds of molecular dyes have been reported for applications in electronic memory. [10,[18][19][20][21] For instance, the azobenzene group is widely adopted in molecular skeletons owing to its excellent photoelectric properties.…”
Section: Introductionmentioning
confidence: 99%